New Multipolarity in Contemporary European Union’s Foreign Policy Discourse - Lyudmila O. Igumnova (СибСкрипт)
Amid the ongoing qualitative transformation of the international system, the leaders of the European Union go beyond day-to-day political agenda, attempting to describe the emerging global geopolitical landscape. The article explores the vision of the contemporary world order and the EU’s role in it as released by its officials. The analysis of the EU’s official discourse provides insight into the ideas that shape Brussels’ policy of adaptation to the changing environment, and allows to identify the theory that best explains the EU’s foreign policy trajectory. Methodologically the article is based on statements made by senior EU officials in 2023-2024, e.g., High Representative for Foreign Affairs and Security Policy Josep Borrell, President of the European Commission Ursula von der Leyen, etc. In describing the world as multipolar, EU leaders attend to different aspects of today's multipolarity. The analysis shows that systemic geopolitical pressure exerts significant impact on the EU’s foreign policy and positioning, therefore purely endogenous approaches are insufficient for a comprehensive study of the Union’s actorness. The discourse combines elements of realist and normative logics. On the one hand, Brussels address the balance of power and various dimensions of security. On the other hand, it projects common values, multilateralism, and partnership. Debates about the EU’s actorness seem more fruitful if they imply convergence of different theories: deep understanding of global dynamic and intra-European specifics, as well as normative and strategic behavioral logics.